Conservation of Modern Oil Paintings - van den Berg, Klaas Jan; Bonaduce, Ilaria; Burnstock, Aviva; Ormsby, Bronwyn; Scharff, Mikkel; Carlyle, Leslie; Heydenreich, Gunnar; Keune, Katrien (Springer International Publishing : Imprint: Springer, 2019)
Artists' oil paints have become increasingly complex and diverse in the 20th Century, applied by artists in a variety of ways. This has led to a number of issues that pose increasing difficulties to conservators and collection keepers. A deeper knowledge of the artists' intent as well as processes associated with material changes in paintings is important to conservation, which is almost always a compromise between material preservation and aesthetics. This volume represents 46 peer-reviewed papers presented at the Conference of Modern Oil Paints held in Amsterdam in 2018. The book contains a compilation of articles on oil paints and paintings in the 20th Century, partly presenting the outcome of the European JPI project 'Cleaning of Modern Oil Paints'. It is also a follow-up on 'Issues in Contemporary Oil Paint' (Springer, 2014). The chapters cover a range of themes and topics such as: patents and paint manufacturing in the 20th Century; characterization of modern-contemporary oil paints and paint surfaces; artists' materials and techniques; the artists' voice and influence on perception of curators, conservators and scientists; model studies on paint degradation and long term stability; approaches to conservation of oil paintings; practical surface treatment and display. The book will help conservators and curators recognise problems and interpret visual changes on paintings, which in turn give a more solid basis for decisions on the treatment of these paintings. .